SISTEM JARINGAN PASOK DAN NILAI TAMBAH EKONOMI KOPI ORGANIK (Study Kasus di KBQ Baburrayan Kabupaten Aceh Tengah) - Mujiburrahmad Mujiburrahmad (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2011)
Supply Network System and Economic Value Added of Organic Coffee (A Case study of KBQ Baburayyan, Aceh Tengah District)ABSTRACT. The aim of this study is to understand the supply chain and economic value added of supply of organic coffee involving various agencies. Research has been done with a combination of surveys and focus group discussions at two points of organic coffee production centers. Results showed that supply network of raw material in Cooperative Baitul Qiradh Baburrayyan (KBQ) came from collectors contracted by the principle of partnership. Those collectors received raw materials from farmers in each cluster and they were supervised by KBQ. The supply networks of coffee in KBQ consisted of two types of channels: (a) domestic channel and (b) export channels. In the domestic channels, coffees were auctioned by inviting local buyers. Economic value added obtained by KBQ was much larger than the collectors. This is due to the more complex of roles undertaken by KBQ. Hence to increase collector and farmers' incomes, the more complex roles should be applied.